2017
DOI: 10.1097/aia.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Cardiac Surgery: An Update on Clinical Implications

Abstract: BackgroundTremendous changes have occurred in enhanced recovery after surgery (ERAS) since Danish surgeon Dr Kehlet published his landmark article in 1997, emphasizing that major surgical procedures may lead to significant undesirable sequelae, including infection, pain, hemorrhage, cardiopulmonary and thromboembolic complications, ileus, postoperative nausea and vomiting, fatigue, and prolonged convalescence. 1 In this regard, the surgical stress response and its subsequently increased demands on organ functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…However, the ERAS protocols are all linked by a set of unifying objectives-the reduction in the stress response of patients to surgery and the speedy resumption of normal daily function. 1,3,7,11,[20][21][22][23] The attenuation of patient stress via ERAS is aimed at minimizing the postoperative catabolic state experienced by the patient, which can lead to the detrimental outcomes of insulin resistance, muscle loss, infection, and delays in wound and anastamotic healing, [20][21][22] inevitably leading to prolonged recovery and extended hospital stays and costs. ERAS protocols can be divided into three time points-preoperative, intraoperative, and postoperative; the key elements which unify the different ERAS guidelines will be discussed here.…”
Section: Eras Protocols and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the ERAS protocols are all linked by a set of unifying objectives-the reduction in the stress response of patients to surgery and the speedy resumption of normal daily function. 1,3,7,11,[20][21][22][23] The attenuation of patient stress via ERAS is aimed at minimizing the postoperative catabolic state experienced by the patient, which can lead to the detrimental outcomes of insulin resistance, muscle loss, infection, and delays in wound and anastamotic healing, [20][21][22] inevitably leading to prolonged recovery and extended hospital stays and costs. ERAS protocols can be divided into three time points-preoperative, intraoperative, and postoperative; the key elements which unify the different ERAS guidelines will be discussed here.…”
Section: Eras Protocols and Recommendationsmentioning
confidence: 99%
“…50 It has been identified that careful attention to fluid balance is an especially important consideration during procedures such as cardiac surgery with cardiopulmonary bypass, where up to 2 L of priming fluid are routinely used, putting patients at an elevated risk for developing complications. 20 Current ERAS guidelines have even outlined the use of transesophageal doppler for the monitoring of patient fluids, in high-risk cases. 12,20…”
Section: Management Of Fluid Balance and Hemostasismentioning
confidence: 99%
See 2 more Smart Citations
“…ERAS is a multimodal, multidisciplinary initiative to improve perioperative care with the effect of substantial improvements in clinical outcomes and cost savings [ 21 ]. It is especially relevant to cardiac surgery and includes issues related to human nutrition and metabolism during the preoperative preparation (fasting, preoperative carbohydrate treatment), intraoperative management (blood glucose monitoring and treatment) and postoperative approach (treatment of nausea and vomiting, early nutrition and gastrointestinal stimulation) [ 22 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%